Artificial Intelligence, Cybersecurity and Cyber Defence - Ventre, Daniel (John Wiley & Sons, Incorporated, 2020)
This book explains the appropriation of artificial intelligence by military organizations, but also law enforcement agencies and the police; to discuss the questions that the development of artificial intelligence. --